1987
DOI: 10.1099/00221287-133-10-2727
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Xanthomonas campestris pathovar campestris with Plasmid DNA

Abstract: Procedures for the introduction of plasmid DNA into Gram-negative bacteria have been adapted and optimized to permit transformation of the plant pathogen Xanthomonas campestris pathovar campestris with the cloning vector pKT230 and other broad-host-range plasmids. The technique involves CaC1,-induced competence and heat shock and is similar to that routinely used for Escherichia coli. Wild-type X . c. campestris strains appear to restrict incoming unmodified DNA, so that plasmid DNA for transformation must be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The properties of commonly used mutagenic agents and the types of mutations induced by them have been discussed (Carlton and Brown, 1981) and summarized (Chatterjee and Vidaver, 1986). Physicochemical agents have been used for mutagenesis of xanthomonads (Whitfield et al, 1981;Tsuchiya et al, 1982;Daniels et al, 1984a;Atkins et al, 1987;Harding et al, 1987;Thorne et al, 1987;Mellano and Cooksey, 1988;. Physicochemical agents have been used for mutagenesis of xanthomonads (Whitfield et al, 1981;Tsuchiya et al, 1982;Daniels et al, 1984a;Atkins et al, 1987;Harding et al, 1987;Thorne et al, 1987;Mellano and Cooksey, 1988;.…”
Section: Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of commonly used mutagenic agents and the types of mutations induced by them have been discussed (Carlton and Brown, 1981) and summarized (Chatterjee and Vidaver, 1986). Physicochemical agents have been used for mutagenesis of xanthomonads (Whitfield et al, 1981;Tsuchiya et al, 1982;Daniels et al, 1984a;Atkins et al, 1987;Harding et al, 1987;Thorne et al, 1987;Mellano and Cooksey, 1988;. Physicochemical agents have been used for mutagenesis of xanthomonads (Whitfield et al, 1981;Tsuchiya et al, 1982;Daniels et al, 1984a;Atkins et al, 1987;Harding et al, 1987;Thorne et al, 1987;Mellano and Cooksey, 1988;.…”
Section: Mutationmentioning
confidence: 99%
“…(Corey and Starr, 1957a,b;Yamasaki et al, 1966;Gabriel, 1984;Atkins et al, 1987;Murooka et al, 1987). Many xanthomonads do not respond to chemical treatments that induce competence necessary for transformation in other bacteria.…”
Section: (D) Transformation and Electrotransformationmentioning
confidence: 99%
“…4), it can be confirmed that the pathogen invades through the stomata, colonizes the intercellular space for multiplication and spreads systemically throughout the whole plant via the leaf veins. Electroporation with plasmid DNA on other Xanthomo-nas species has been carried out in previous investigations for the purpose of specific detection of the pathogen (Atkins et al, 1987;Yang et al, 1991). In a previous study with GFP-tagged X. fragariae by Kaste- 2013), a slightly lower virulence of the tagged strain was reported, but this was not found in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of plasmid pMA36 into the cured strain was performed with some modification of the method described by Atkins et al (1987). Plasmid-cured log phase cells (5 ml) of Xoo were added to 50 ml of prewarmed Luria broth in a 250 ml Erlenmeyer flask and kept in an orbital shaker (30"C, 200 rev min-').…”
Section: Plasmid Transformationmentioning
confidence: 99%